(3QSGdI GdJbOjS OYGA GdSGObjf (B( (3OYGA dfLGI GdehMOjf GdYGQajf (B)s - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdMGce GdeYHhO hMOg GdefLR dYHOg GdEeGe GdgGOi hYOg JhcdJ Ydi ehdGfG MGce GdYbd s
(3BNQgG (B:s
(3hCegdfG GdEfLGR hYOc GdChdjGFc GdeNdUjf Efc Ydi Pcd bOjQ hHELGHI gPG GdbSe hHELdGd ChdgjJc cajd LOjQ Je GdJbOjS hGdMeO dehdGfG hMOg hgh MSHi hfYe GdeYjf GdfUjQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B32s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds